Temperature-responsive macromolecules that promote bone formation

Injectable, temperature-responsive PPCN-based hydrogels address the limitations of current bone repair materials by providing controlled release of bioactive agents to promote bone formation and repair, effectively inducing stem cells to become bone cells and accelerating healing.

JP7653696B2Active Publication Date: 2025-03-31NORTHWESTERN UNIV

Patent Information

Application Number
JP2019531139
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-10-12
Filing Date
2017-12-08
Publication Date
2025-03-31
Estimated Expiration
2037-12-08

AI Technical Summary

Technical Problem

Current materials for bone repair and regeneration are often biologically inert or fragile, lacking the ability to induce bone formation and address issues like inflammation and osteoporotic bone, and they do not allow for local drug delivery or minimal invasive techniques.

Method used

Development of injectable, temperature-responsive PPCN-based hydrogels that are liquid at room temperature and gel at body temperature, allowing for controlled release of therapeutic agents, such as β-glycerophosphate, strontium, and cRGD peptides, to promote bone formation and repair.

Benefits of technology

The PPCN-based hydrogels effectively promote bone formation and repair by providing a controlled release of bioactive agents, inducing stem cells to become bone cells, and accelerating healing in various bone species, while also allowing for local drug delivery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653696000004
    Figure 0007653696000004
  • Figure 0007653696000005
    Figure 0007653696000005
  • Figure 0007653696000006
    Figure 0007653696000006
Patent Text Reader

Abstract

The present disclosure provides injectable, thermoresponsive hydrogels that are liquid at room temperature and can be used as carrier materials, gel at body temperature, and enable controlled release. In particular, the present disclosure provides PPCN-based hydrogels that have therapeutic agents (e.g., drugs, ions, etc.) incorporated therein or attached thereto, as well as methods for preparing the same and their use for, for example, promoting bone formation / repair and / or treating bone diseases.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 62 / 432,266, filed December 9, 2016, and U.S. Provisional Patent Application No. 62 / 571,495, filed October 12, 2017, both of which are incorporated by reference in their entireties.

[0002] The present disclosure provides injectable thermoresponsive hydrogels that are liquid at room temperature and can be used as carrier materials, and gel at body temperature to allow controlled release. In particular, the present disclosure provides PPCN-based hydrogels with therapeutic agents (e.g., drugs, ions, etc.) incorporated therein or loaded thereon, as well as methods for preparing the same and methods for using the same, for example, for promoting bone formation / repair and / or treating bone diseases. [Background technology]

[0003] In the field of bone tissue regeneration, there has been an increasing emphasis on the development of materials for bone defect repair. Very few studies have been conducted on bone diseases. Thus, the main focus has been on the strength of the materials rather than their osteogenic induction potential. These materials are often hard filler pastes that are biologically inert (e.g., methyl methacrylate) or brittle (e.g., calcium phosphate). Moreover, the challenges of inflammation and osteoporotic bone are largely unexplored. There remains an unmet need for materials that can be used with minimally invasive procedures and adapted to the specific fracture site, that can interact with the complex cellular environment to accelerate healing in all bone types, induce stem cells to become osteocytes, and allow for local drug delivery when required. Summary of the Invention

[0004] The present disclosure provides injectable thermoresponsive hydrogels that are liquid at room temperature and can be used as carrier materials, and gel at body temperature to allow controlled release. In particular, the present disclosure provides PPCN-based hydrogels with therapeutic agents (e.g., drugs, ions, etc.) incorporated therein or loaded thereon, as well as methods for preparing the same and methods for using the same, for example, for promoting bone formation / repair and / or treating bone diseases.

[0005] In some embodiments, provided herein are compositions comprising a PPCN-based hydrogel comprising citric acid, poly(ethylene glycol), glycerol 1,3-diglycerolate diacrylate, and poly(N-isopropylacrylamide) monomers, and at least one bioactive agent incorporated therein and / or attached thereto. In some embodiments, the bioactive agent is an additional monomer incorporated within the PPCN-based hydrogel backbone. In some embodiments, the bioactive agent is β-glycerophosphate. In some embodiments, the bioactive agent is a pendant group attached to the PPCN hydrogel. In some embodiments, the pendant group is a small molecule. In some embodiments, the pendant group is a peptide. In some embodiments, the bioactive agent is a cyclic Arg-Gly-Asp (cRGD) peptide. In some embodiments, the bioactive agent is an ionic crosslinker. In some embodiments, the bioactive agent is Ca 2+ , B.A. 2+ , or Sr 2+ It is.

[0006] In some embodiments, the present disclosure provides a composition comprising a PPCN-based phosphate-displayed hydrogel that includes monomers of citric acid, poly(ethylene glycol), glycerol 1,3-diglycerolate diacrylate, poly(N-isopropylacrylamide), and β-glycerophosphate. In some embodiments, the PPCN-based phosphate-displayed hydrogel has the structure

[0007] [ka]

[0008] where x and y are, independently, 2 to 20. In some embodiments, the composition is prepared by (a) polycondensation of citric acid, poly(ethylene glycol), glycerol 1,3-diglycerolate diacrylate, and β-glycerophosphoric acid monomers, followed by (b) free radical polymerization with poly(N-isopropylacrylamide). In some embodiments, the composition is prepared by the reaction shown in Scheme 1.

[0009] In some embodiments, provided herein are compositions comprising PPCN-based peptide-displaying hydrogels comprising monomers of citric acid, poly(ethylene glycol), glycerol 1,3-diglycerolate diacrylate, and poly(N-isopropylacrylamide), and a peptide covalently conjugated to a carboxy group of the citric acid monomer. In some embodiments, the peptide is covalently conjugated to a carboxy group of the citric acid monomer via carbodiimide chemistry. In some embodiments, the peptide is cyclic Arg-Gly-Asp (cRGD). In some embodiments, the cRGD is covalently conjugated to a carboxy group of the PPCN. In some embodiments, the composition is prepared by the reaction shown in Scheme 2.

[0010] In some embodiments, provided herein are compositions comprising a PPCN-based hydrogel comprising monomers of citric acid, poly(ethylene glycol), glycerol 1,3-diglycerolate diacrylate, and poly(N-isopropylacrylamide) and a metal ion crosslink. In some embodiments, the composition comprises a metal ion crosslinked PPCN. In some embodiments, the composition is prepared by incubating PPCN in the presence of a salt of a metal ion. In some embodiments, the metal ion is Ca 2+ , B.A. 2+ , or Sr 2+ It is.

[0011] In some embodiments, the present specification provides a method of promoting bone repair, comprising administering a composition described herein (e.g., a PPCN-based hydrogel) to a fracture site or diseased site of a bone and allowing the composition to gel.

[0012] In some embodiments, the present description provides uses of the compositions described herein (eg, PPCN-based hydrogels) to promote bone repair. [Brief description of the drawings]

[0013] [Figure 1] (a) Major peaks in the MALDI spectrum of PPCN-cRGD include the expected ionized cyclic-RGDfC at 581.7 m / z and the complete monomer at 1156 m / z. (b) ICP-OES study of 50 and 100 mM Sr2+ release from PPCN-Sr gels shows that most of the strontium is released over a one week period. FT-IR of PPCN-phos shows the growth of a peak associated with the reagent β-glycerophosphate, i.e., a broadening of the OH stretch, at 3400 nm-1, and a new peak at around 1238 nm-1 due to the phosphonate. Elemental analysis corroborates this data, with a small loss of carbon due to the replacement of carbon-rich PEG chains with β-glycerophosphate. [Diagram 2] Rheological characterization of PPCN (a), compared with PPCN-cRGD (b), PPCN-Sr (c) and PPCN-phos (d), confirms that all three osteoinductive variants maintain thermoresponsive behavior and exhibit lower LCST transitions than PPCN. [Diagram 3]LIVE / DEAD imaging of hMSC and MC3T3 seeded in 3D gels and cultured in regular DMEM. Cells were seeded in either alginate, PPCN, PPCN-cRGD, PPCN-Sr, or PPCN-phos gels. Cells grown in PPCN-cRGD gels show spreading morphology, confirming that RGD functionality is preserved after complexation with PPCN. Viability is >75% in all gels. Images were taken on day 10 and representative images from triplicate wells are shown. [Figure 4] Alkaline phosphatase (ALP) activity of (a) hMSC and (b) MC3T3 on days 3 and 10 is shown. No significant increase in ALP was detected in hMSC on day 10. However, a significant increase in ALP was detected in both MC3T3 grown in PPCN-Sr gel and PPCN-phos gel. *P value < 0.05 and **P value < 0.01. [Diagram 5] Characterization of hMSCs at day 21 by staining with Alizarin Red S for calcium deposition and immunohistochemical staining for both osteopontin (OPN) and osteocalcin (OCN). Corresponding quantification is shown to the right. Mineralization is seen in all three functionalizations. Data show that osteopontin expression is highest in PPCN-Sr and osteocalcin expression is highest in PPCN-phos. [Figure 6] Micro-CT analysis of PPCN and PPCN-Sr injected intramuscularly in the thigh from day 0 to day 42. The top right panel shows the thigh of a mouse with aligned micro-CT images. The bottom right panel shows quantification of micro-CT images (n=3). Calcification was observed in the PPCN-Sr group starting at day 10 and increasing consistently throughout the 6 weeks. No calcification was observed in the non-functionalized PPCN control. The area of ​​calcification was quantified using threshold intensity in Osirix and reconstructed to show the 3D inset image. [Figure 7]Compared to PPCN controls (a), PPCN-Sr shows significant osteocalcin expression and cell infiltration (b). Alizarin red S staining to examine mineralization also shows that PPCN-Sr (d) shows strong mineralization as detected by red calcium deposits compared to non-functionalized PPCN (c). Whole tissue sections of PPCN and PPCN-Sr, respectively, are shown in (e) and (f). [Figure 8] ICP analysis of organs from eight mice at day 42 shows that strontium is absent from all major organs at the time of digestion (a). Furthermore, XPS analysis of sectioned muscle tissue shows that strontium has been removed and is no longer present at the injection site (b). XPS analysis shows that calcium, phosphate and oxygen content are consistent with calcification in the PPCN-Sr group, but no localized persistence of strontium is evident at week 6.

[0014] definition Although any methods and materials similar or equivalent to those described herein can be used in the practice or testing of the embodiments described herein, some preferred methods, compositions, devices, and materials are described herein. However, before describing the materials and methods of the present application, it should be understood that the present invention is not limited to the specific molecules, compositions, methodologies, or protocols described herein, as they may vary according to routine experimentation and optimization. It should also be understood that the terminology used in the description is for the purpose of describing individual variations or individual embodiments only, and is not intended to limit the scope of the embodiments described herein.

[0015] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. However, in case of conflict, the present specification, including definitions, will take precedence. Therefore, the following definitions apply to the embodiments described herein:

[0016] As used in the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a polymer" is a reference to one or more polymers and equivalents thereof known to those skilled in the art, and so forth.

[0017] As used herein, the term "and / or" includes any combination of the listed items, including any one of the listed items. For example, "A, B, and / or C" includes A, B, C, AB, AC, BC, and ABC, each of which is considered to be separately described by the statement "A, B, and / or C." As used herein, the term "comprise" and linguistic variations thereof refer to the presence of the stated feature(s), element(s), method step(s), etc., and do not exclude the presence of additional feature(s), element(s), method step(s), etc. Conversely, the term "consisting of" and linguistic variations thereof refer to the presence of the stated feature(s), element(s), method step(s), etc., and excludes any unrecited feature(s), element(s), method step(s), etc., except for impurities ordinarily associated therewith. The phrase "consisting essentially of" refers to the recited feature(s), element(s), method step(s), etc., as well as any additional feature(s), element(s), method step(s), etc. that do not materially affect the basic nature of the composition, system, or method. Many embodiments herein are described using the open language "comprising." Such embodiments encompass embodiments using multiple closed language "consisting of" and / or "consisting essentially of," which may otherwise be claimed or described using such language.

[0018] As used herein, the terms "substantially all," "substantially complete," and similar terms refer to greater than 99% and the terms "substantially free," "substantially free," and similar terms refer to less than 1%.

[0019] The term "about" acknowledges some degree of variability in a value or range. As used herein, the term "about" refers to a value within 10% of a stated value or range (e.g., about 50 is equivalent to 45-55).

[0020] As used herein, the term "polymer" refers to a chain of repeating structural units, or "monomers," typically of high molecular weight. Examples of polymers include homopolymers (one type of monomer subunit), copolymers (two types of monomer subunits), and heteropolymers (e.g., three or more types of monomer subunits). As used herein, the term "oligomer" refers to a polymer of just a few monomer units (e.g., 2, 3, 4, 5, or more) up to about 50 monomer units, e.g., dimers, trimers, tetramers, pentamers, hexamers, decamers, etc.

[0021] As used herein, the term "linear polymer" refers to a polymer whose molecules form long chains without branching or crosslinking structures.

[0022] As used herein, the term "branched polymer" refers to a polymer that includes a polymer backbone with one or more additional monomers or chains or monomers extending from the polymer backbone. The degree of "branching" interconnection is insufficient to render the polymer insoluble.

[0023] As used herein, the term "prepolymer" refers to a linear or branched polymer that can be subject to crosslinking under appropriate conditions (e.g., conditions that "cure" and / or form a thermoset or hydrogel) and that has not previously been subjected to appropriate conditions (e.g., not significantly crosslinked).

[0024] As used herein, the term "crosslinked polymer" refers to a polymer in which there is a significant degree of interconnection between multiple polymer chains, resulting in an insoluble polymer network. For example, multiple polymer chains may be crosslinked to each other at points within their structure, not just at the ends of the polymer chains.

[0025] As used herein, the term "biocompatible" refers to a material, compound, or composition that does not cause or induce significant adverse effects when administered to a subject. Examples of possible adverse effects that limit biocompatibility include, but are not limited to, transient inflammation, transient or adverse immune responses, and toxicity.

[0026] As used herein, the term "hydrogel" refers to a three-dimensional (3D) crosslinked network of hydrophilic polymers that swell rather than dissolve in water.

[0027] As used herein, the term "temperature responsive" refers to a material that exhibits a change in physical properties at different temperature ranges. Of particular relevance herein are "temperature responsive phase-transition" materials. "Temperature responsive phase-transition" materials are soluble or in a liquid state at a first temperature range (e.g., 26°C) and insoluble or in a solid state at a second temperature range (e.g., 30-45°C). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] Provided herein are injectable thermoresponsive hydrogels that are liquid at room temperature and can be used as carrier materials for ions or therapeutic agents, and gel at body temperature to allow for controlled release. In some embodiments, the material is an antioxidant and can promote bone formation without the addition of osteogenic factors based on the properties of the material. In some embodiments, the material includes bone promoters, such as, for example, phosphate, cRGD, and / or strontium.

[0029] In some embodiments, the present disclosure provides a temperature-responsive hydrogel comprising monomers of citric acid, poly(ethylene glycol), glycerol 1,3-diglycerolate diacrylate, and poly(N-isopropylacrylamide). In some embodiments, the temperature-responsive hydrogel is a PPCN-based hydrogel. In some embodiments, the PPCN-based hydrogel comprises monomers of citric acid, poly(ethylene glycol), glycerol 1,3-diglycerolate diacrylate, and poly(N-isopropylacrylamide) and one or more additional monomers (e.g., β-glycerophosphate). In some embodiments, the PPCN-based hydrogel comprises monomers of citric acid, poly(ethylene glycol), glycerol 1,3-diglycerolate diacrylate, and poly(N-isopropylacrylamide) and one or more additional monomers (e.g., β-glycerophosphate). In some embodiments, the PPCN-based hydrogel comprises monomers of citric acid, poly(ethylene glycol), glycerol 1,3-diglycerolate diacrylate, and poly(N-isopropylacrylamide) and one or more bioactive substances (e.g., metal ions (e.g., Sr 2+ ), peptides (e.g., cRGD), etc.

[0030] In some embodiments, the negatively charged carboxyl groups of the PPCN-based hydrogel (e.g., on the citrate monomers) can be coupled to positively charged metal ions (e.g., Sr 2+ , Ca 2+ , B.A. 2+ etc. In some embodiments, separate carboxyl groups coordinate to metal ions to provide crosslinking to the PPCN-based polymer. In some embodiments, the materials herein are not limited by the identity of the metal ion. In some embodiments, the metal ion is introduced into the PPCN-based material as a salt.

[0031] In some embodiments, the carboxyl groups of the PPCN-based hydrogel (e.g., displayed on citrate monomers) are conjugated to peptides or bioactive small molecules via a suitable linker chemistry. In some embodiments, suitable chemistries for linking bioactive peptides and / or small molecules to the PPCN-based hydrogel include alkyne / azide, thiol / maleimide, thiol / haloacetyl (e.g., iodoacetyl, etc.), thiol / pyridyl disulfide (e.g., pyridyldithiol, etc.), sulfonyl azide / thioacid, etc.

[0032] In some embodiments, bioactive peptides that promote bone healing and / or repair are complexed with PPCN-based hydrogels. Suitable peptides include P-15 peptide (Bhatnagar et al. Tissue Eng. 1999;5(1):53-65.; incorporated by reference in its entirety), RGD-containing peptides (Ruoslahti & Pierschbacher. Cell. 1986;44(4):517-8.; incorporated by reference in its entirety), GFOGER (Glycine-Phenylalanine-Hydroxyproline-Glycine-Glutamate-Arginine) (SEQ ID NO: 1), collagen binding motif (CBM), DGEA (Asp-Gly-Glu-Ala) (SEQ ID NO: 2), SVVYGLR (Ser-Val-Val-Tyr-Gly-Leu-Arg) (SEQ ID NO: 3), KRSR (Lysine-Arginine-Serine-Arginine) (SEQ ID NO: 4), FHRRIKA (Phe-His-Arg-Arg-Ile-Lys-Ala) (SEQ ID NO: 5), fibronectin (FN)-derived peptides, and other ECM-derived peptides (Pountos et al. BMC Med. 2016;14:103.; incorporated by reference in its entirety).

[0033] In some embodiments, the PPCN or PPCN-based polymer or hydrogel comprises at least 0.1% citric acid monomers (e.g., >0.1%, >0.2%, >0.5%, >1%, >2%, >3%, >4%, >5%, >10%, >20%, >30%, >40%, >50%, >60%, >70%, >80%, >90%, >95%, >98%, >99%). In some embodiments, the polymers herein comprise less than 99% citric acid monomers (e.g., <99%, <98%, <95%, <90%, <80%, <70%, <60%, <50%, <40%, <30%, <20%, <10%, <5%, <4%, <3%, <2%, <1%, <0.5%). In some embodiments, the polymer comprises about 99%, about 98%, about 95%, about 90%, about 80%, about 70%, about 60%, about 50%, about 40%, about 30%, about 20%, about 10%, about 5%, about 4%, about 3%, about 2%, about 1%, or about 0.5% citric acid monomers.

[0034] In some embodiments, the PPCN or PPCN-based polymer or hydrogel comprises at least 0.1% polyethylene glycol monomers (e.g., >0.1%, >0.2%, >0.5%, >1%, >2%, >3%, >4%, >5%, >10%, >20%, >30%, >40%, >50%, >60%, >70%, >80%, >90%, >95%, >98%, >99%). In some embodiments, the polymers herein comprise less than 99% polyethylene glycol monomers (e.g., <99%, <98%, <95%, <90%, <80%, <70%, <60%, <50%, <40%, <30%, <20%, <10%, <5%, <4%, <3%, <2%, <1%, <0.5%). In some embodiments, the polymer comprises about 99%, about 98%, about 95%, about 90%, about 80%, about 70%, about 60%, about 50%, about 40%, about 30%, about 20%, about 10%, about 5%, about 4%, about 3%, about 2%, about 1%, or about 0.5% polyethylene glycol monomers.

[0035] In some embodiments, the PPCN or PPCN-based polymer or hydrogel comprises at least 0.1% (e.g., >0.1%, >0.2%, >0.5%, >1%, >2%, >3%, >4%, >5%, >10%, >20%, >30%, >40%, >50%, >60%, >70%, >80%, >90%, >95%, >98%, >99%) glycerol 1,3-diglycerolate diacrylate monomer. In some embodiments, the polymers herein comprise less than 99% (e.g., <99%, <98%, <95%, <90%, <80%, <70%, <60%, <50%, <40%, <30%, <20%, <10%, <5%, <4%, <3%, <2%, <1%, <0.5%) of glycerol 1,3-diglycerolate diacrylate monomer. In some embodiments, the polymers comprise about 99%, about 98%, about 95%, about 90%, about 80%, about 70%, about 60%, about 50%, about 40%, about 30%, about 20%, about 10%, about 5%, about 4%, about 3%, about 2%, about 1%, or about 0.5% of glycerol 1,3-diglycerolate diacrylate monomer.

[0036] In some embodiments, the PPCN or PPCN-based polymer or hydrogel comprises at least 0.1% N-isopropylacrylamide monomers (e.g., >0.1%, >0.2%, >0.5%, >1%, >2%, >3%, >4%, >5%, >10%, >20%, >30%, >40%, >50%, >60%, >70%, >80%, >90%, >95%, >98%, >99%). In some embodiments, the polymers herein comprise less than 99% N-isopropylacrylamide monomers (e.g., <99%, <98%, <95%, <90%, <80%, <70%, <60%, <50%, <40%, <30%, <20%, <10%, <5%, <4%, <3%, <2%, <1%, <0.5%). In some embodiments, the polymer comprises about 99%, about 98%, about 95%, about 90%, about 80%, about 70%, about 60%, about 50%, about 40%, about 30%, about 20%, about 10%, about 5%, about 4%, about 3%, about 2%, about 1%, or about 0.5% N-isopropylacrylamide monomers.

[0037] In some embodiments, the materials described herein include composites of the PPCN-based thermoresponsive hydrogel materials described herein and one or more additional components, in some embodiments, the additional components comprise 1-99% by weight of the composite (e.g., 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 96%, 97%, 98%, 99%, or any range therebetween). In some embodiments, the composite material comprises at least 1% PPCN-based hydrogel (e.g., >1%, >2%, >3%, >4%, >5%, >10%, >20%, >30%, >40%, >50%, >60%, >70%, >80%, >90%, >95%, >98%, >99%). In some embodiments, the temperature-responsive composite material comprises less than 99% PPCN-based hydrogel (e.g., <99%, <98%, <95%, <90%, <80%, <70%, <60%, <50%, <40%, <30%, <20%, <10%, <5%, <4%, <3%, <2%, <1%). In some embodiments, the composite material comprises about 99%, about 98%, about 95%, about 90%, about 80%, about 70%, about 60%, about 50%, about 40%, about 30%, about 20%, about 10%, about 5%, about 4%, about 3%, about 2%, about 1%, or any range therebetween of PPCN-based hydrogel, where the aforementioned percentages may be by weight or by mole.

[0038] In some embodiments, a composite material is provided of a temperature-responsive PPCN-based hydrogel material and a bioceramic component. Suitable bioceramics include hydroxyapatite (HA; Ca 10 (PO4)6(OH)2), tricalcium phosphate beta (β-TCP; Ca3(PO4)2), and a mixture of HAP and β-TCP.

[0039] In some embodiments, the composite material comprises a PPCN-based hydrogel and one or more additional polymeric components. Suitable biodegradable polymers include collagen, elastin, hyaluronic acid and derivatives, sodium alginate and derivatives, chitosan and derivatives, gelatin, starch, cellulose polymers (e.g., methylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose, carboxymethylcellulose, cellulose acetate phthalate, cellulose acetate succinate, hydroxypropylmethylcellulose phthalate), casein, dextran and derivatives, polysaccharides, poly(caprolactone), fibrinogen, poly(hydroxy acids), poly(L-lactide), poly(D,L-lactide), poly(D,L-lactide-co-glycolide), poly(L-lactide-co-glycolide), copolymers of lactic acid and glycolic acid, copolymers of ε-caprolactone and lactide, copolymers of glycolide and ε-caprolactone, and copolymers of ε-caprolactone and lactide. Non-limiting examples include copolymers of prolactone, copolymers of lactide and 1,4-dioxan-2-one, polymers and copolymers containing one or more residue units of D-lactide, L-lactide, D,L-lactide, glycolide, ε-caprolactone, trimethylene carbonate, 1,4-dioxan-2-one, or 1,5-dioxepan-2-one monomers, poly(glycolide), poly(hydroxybutyric acid), poly(alkylcarbonates) and poly(orthoesters), polyesters, poly(hydroxyvaleric acid), polydioxanones, poly(ethylene terephthalate), poly(malic acid), poly(tartronic acid), polyanhydrides, polyphosphazenes, poly(amino acids), and copolymers of the foregoing polymers, as well as blends and combinations of the foregoing polymers.(For general information, see Illum, L., Davids, SS (eds.) "Polymers in Controlled Drug Delivery" Wright, Bristol, 1987; Arshady, J. Controlled Release 17:1-22, 1991; Pitt, Int. J. Phar. 59:173-196, 1990; Holland et al., J. Controlled Release 4:155-0180, 1986, which are incorporated by reference in their entireties.) Suitable non-biodegradable polymers include silicone rubber, polyethylene, acrylic resins, polyurethanes, polypropylene, and polymethyl methacrylate.

[0040] As described throughout, the present specification provides PPCN-based materials, including hardenable (e.g., temperature-responsive) hydrogels and / or composites thereof. These materials find use in a variety of applications, including any application in which it is desired to administer a material in liquid and / or soluble form and then become solid and / or insoluble (over a short period of time) when exposed to desired conditions (e.g., physiological temperatures). The materials described herein find use in, for example, medical and dental bone repair applications, such as repair of craniofacial injuries, stabilization of complex fractures, promotion of bone growth, bone regeneration, as bone substitutes, for implant attachment, and the like. In some embodiments, the materials find use in non-medical / dental applications. In some embodiments, the PPCN-based materials described herein are liquid at or below physiological temperatures (e.g., 36°C, 35°C, 34°C, 33°C, 32°C, 31°C, 30°C, 29°C, 28°C, 27°C, 26°C, 25°C, 24°C, 23°C, 22°C, 21°C, 20°C, or lower or ranges therebetween). In some embodiments, the PPCN-based materials described herein are gels at or near physiological temperatures (e.g., 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, or ranges therebetween).

[0041] In some embodiments where the materials herein are used for bone or fracture / injury repair, stabilization, regeneration, growth, etc., the materials further comprise an additional component / agent that promotes incorporation into the bone, bone growth, bone regeneration, etc. In some embodiments, the additional component / agent is incorporated into the material and then encapsulated within the material upon hardening. In such embodiments, the additional component / agent is non-covalently associated with the PPCN-based hydrogel and other components of the material. In other embodiments, the additional component / agent is covalently linked to the PPCN-based hydrogel.

[0042] In some embodiments, the materials described herein are utilized in the delivery of growth factors or other bioactive substances for the repair of bone defects and / or regeneration of bone. Suitable agents for use in the embodiments herein include, but are not limited to, bone morphogenetic proteins (e.g., BMP-1, BMP-2, BMP-4, BMP-6, and BMP-7); members of the transforming growth factor beta (TGF-β) superfamily, including but not limited to TGF-β1, TGF-β2, and TGF-β3; growth differentiation factors (GDF1, GDF2, GDF3, GDF5, GDF6, GDF7, myostatin / GDF8, GDF9, GDF10, GDF11, and GDF15); vascular endothelial growth factor (VEGF); fibroblast growth factor (FGF), and the like. These or other agents can be covalently linked to the materials described herein or components thereof, non-covalently associated with moieties displayed on the materials described herein or components thereof, embedded within the materials described herein, and the like.

[0043] In some embodiments, the PPCN-based hydrogels herein are utilized as carriers of therapeutic agents (e.g., osteoporosis drugs), cells (e.g., stem cells), growth factors, etc. In some embodiments, the PPCN-based hydrogels herein provide localized controlled delivery of bioactive agents encapsulated therein.

[0044] In some embodiments, the present specification provides a method comprising administering to a bone defect or fracture a composition comprising a PPCN-based hydrogel described herein. In some embodiments, the present specification provides a method for using a PPCN-based hydrogel described herein to repair a bone defect or fracture.

[0045] In some embodiments, the PPCN-based hydrogels described herein are injected into the site of a fracture (eg, during orthopedic surgery) to promote and / or accelerate healing. EXAMPLES

[0046] experiment cell culture For the gel studies, human mesenchymal stem cells (hMSCs, ATCC) were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% FBS and 5 ml of 10x penicillin-streptomycin, but no other osteogenic factors. The hMSCs used in these studies were no older than passage 6. Mouse pre-osteoblastic MC3T3-E1 cells (ATCC) were cultured in DMEM:F12. Both cell lines were cultured at 37°C with 5% carbon dioxide (CO2).

[0047] Materials preparation and characterization PPCN (poly(polyethylene glycol·citric acid-co-N-isopropylacrylamide)) was prepared by polycondensation followed by radical polymerization.

[0048] To prepare PPCN-phos, the original PPCN synthesis was adjusted to add 0.1 molar ratio of β-glycerophosphate in the first polycondensation step (Scheme 1), while the subsequent reaction steps were unchanged.

[0049] [ka]

[0050] To prepare PPCN-cRGD gels, PPCN was generated as reported. Cyclic RGDfC peptide (ABI Scientific) was then covalently conjugated to the available carboxy groups of citrate in the PPCN polymer chain via maleimide chemistry (Scheme 2). The intended concentration of cyclic RGD peptide was 10%.

[0051] [ka]

[0052] To prepare the PPCN-Sr gel, PPCN was dissolved in PBS (1x) at 100 mg / ml. 100 mM SrCl26H2O (Sigma) was mixed into the PPCN / PBS solution and left at 4 °C overnight for cross-linking (Scheme 2).

[0053] Characterization of the gel is shown in Figure 1. PPCN-cRGD complexation was confirmed by matrix-assisted laser desorption / ionization (MALDI) (Figure 1a). Samples were prepared using an alpha-cyano-4-hydroxycinnamic acid matrix. PPCN-Sr was characterized by a strontium release test using an inductively coupled plasma optical emission spectrometry (Thermo iCAP 7600 ICP-OES). The gel was immersed in simulated body fluid, the solution was removed for 14 days, and Sr was detected. 2+ The gels were assayed for concentration (Figure 1b). PPCN-phos was characterized by FT-IR (Bruker Tensor37) and XPS (Figure 1c). Further rheological characterization was performed on a TA Instruments DHR rheometer using a 20 mm, 2° cone-peltier plate geometry and a solvent trap cover to minimize sample evaporation. The gels were tested in temperature ramp experiments from 15°C to 45°C at a heating rate of 5°C / min. Viscoelastic moduli were monitored by applying an angular frequency of 10 rad / sec and a strain amplitude of 5%. A gap height of 52 μm was used for all samples. The initial change in viscoelastic properties was characterized by the increase in storage modulus (G') relative to loss modulus (G'').

[0054] 3D Differentiation Test Cells were encapsulated with various temperature-responsive PPCN solutions, prepared by dissolving PPCN at 100 mg / mL in PBS (1x). Cells were encapsulated at 1x10 cells / mL of liquid PPCN. 5 The cells were added to the solution by homogenous mixing at a concentration of 100x ...

[0055] Bone differentiation assay For early detection of osteogenic differentiation (Figure 4), alkaline phosphatase (ALP) was measured. Gels were taken on days 3 and 10, and extracellular alkaline phosphatase (ALP) activity was detected using a fluorometric quantification kit (Biovision). The non-fluorescent substrate 4-methylumbelliferyl phosphate disodium salt (MUP) was added and cleaved by ALP to obtain a fluorescent signal (Ex / Em=360 / 440 nm). Fluorescence was read using a microplate reader. Enzyme activity was calculated based on serially diluted gel standards and normalized to total DNA content using a simultaneous Quant-iT PicoGreen assay (Thermo Fisher).

[0056] For late detection of bone differentiation (Figure 5), Alizarin Red S staining and immunohistochemistry for osteocalcin (OCN) and osteopontin (OPN) were performed. For Alizarin Red S, cells were fixed inside a pre-warmed gel, stained through the gel, and then washed several times with DI water to rinse off excess stain. Calcification was visualized under a light microscope. For immunohistochemistry, cells were fixed inside a pre-warmed gel, primary antibodies for OPN or OCN were added, and counterstained with DAPI.

[0057] calcification To assess mineralization, mice were anesthetized with isoflurane and placed on a heated micro-CT table. Images were acquired with a preclinical microPET / CT imaging system nanoScan scanner (Mediso-USA, Boston, MA). Data were acquired with medium magnification, 33 μm focus, 1 × 1 binning, 720 projections across the circumference, and an exposure time of 300 ms. Images were acquired using 35 kVp. Projection data were reconstructed using Mediso filtered backprojection software with a voxel size of 68 μm. Reconstructed data were displayed and segmented with Osirix Lite for Mac. Images were quantified by creating regions of interest (ROIs) using a 2D region grow using a lower threshold of 600 Hounsfield units (HU) and an upper threshold of 10,000 Hounsfield units using the coronal plane. Mineralization was quantified using the ROIs and calculating the mean HU of each ROI (bones, 700–3,000 HU).

[0058] Immunofluorescence Animals were euthanized by carbon dioxide inhalation. Tissues were harvested and fixed overnight at 4°C in 4% paraformaldehyde in PBS. Samples were washed in several changes of PBS to remove residual paraformaldehyde. Samples were dehydrated in an ethanol series, removed in xylene, and embedded in paraffin. Five-micron-thick sections were cut and mounted on slides. Sections were treated with xylene to remove paraffin and rehydrated with alternating ethanol and water. Slides were immersed in antigen retrieval buffer (10 mM sodium citrate, 0.05% Tween 20, pH 6.0) and heated at 100°C for 15 min. After washing with PBS, samples were blocked for 30 min in PBS containing 5 mg / mL BSA, 5% normal goat serum. Samples were incubated overnight at 4°C with primary antibodies diluted in blocking buffer. Slides were washed three times with PBS (5 min each time) and then incubated with secondary antibodies diluted in blocking buffer for 30 min at room temperature. Slides were washed six times with PBS (5 min each time) and then mounted with antifade mounting medium and sealed with nail polish. Images were acquired with a Nikon TE-2000U microscope or a Cytation5 image reader.

[0059] Strontium Distribution Strontium distribution was assayed in several major organs, namely heart, brain, spleen, testes, muscle, lung, kidney, and liver. After euthanasia, each organ was harvested and stored at -80°C until analysis. Tissue digestion was performed by adding 70% nitric acid and 37% hydrogen peroxide to each sample. After 1 hour, the samples were uncapped to allow accumulated gas to escape. The tissue was left to digest for 2 days at room temperature. After 2 days, samples were diluted to 2.4% acid with MQ water and prepared for ICP-OES as described above.

[0060] elemental analysis XPS analysis of sectioned tissues was performed on a Thermo Fisher ESCALab 250Xi using an Al K-alpha X-ray source (1486.6 eV) (Thermo Fisher Scientific, Waltham MA). The monochromated X-ray beam spot size was 300 μm in diameter and the power was 100 watts. A pass energy of 100 eV and a step size of 1 eV were used for the survey scan. A pass energy of 50 eV and a step size of 0.1 eV were used for the high-resolution scan. The acquisition time was 50 ms. XPS spectra were calibrated with the contaminating carbon peak at 284.8 eV. All XPS data were processed with Avantage software.

Claims

1. 1. A composition for use in promoting bone repair comprising a PPCN-based phosphate-exposing hydrogel, the hydrogel being a free radical polymerization product of a polycondensate of monomers of citric acid, poly(ethylene glycol), glycerol 1,3-diglycerolate diacrylate, and β-glycerophosphoric acid with a monomer of N-isopropylacrylamide, The PPCN-based phosphate-exposed hydrogel is a covalently linked polymer of citric acid, poly(ethylene glycol), glycerol 1,3-diglycerolate diacrylate, N-isopropylacrylamide, and β-glycerophosphate.

2. The method comprises the steps of: (a) polycondensing citric acid, poly(ethylene glycol), glycerol 1,3-diglycerolate diacrylate, and β-glycerophosphoric acid monomers, followed by (b) free radical polymerization of the polycondensate obtained in step (a) with N-isopropylacrylamide monomer, preparing a polymer of citric acid, poly(ethylene glycol), glycerol 1,3-diglycerolate diacrylate, N-isopropylacrylamide, and β-glycerophosphate covalently linked thereto; A method for producing the composition of claim 1.

Citation Information

Patent Citations

  • hardenable ceramic hydraulic cement

    JP2002527208A

  • Fibrin composition containing strontium compounds

    JP2010525070A

  • Bioactive nanocomposite materials

    JP2010537763A

Cited By

  • Biological implant and surgical instrument

    WO2025169469A1